Citizen scientists and non-citizen scientist hobbyists: motivation, benefits, and influences. Issue 4 (2nd October 2018) - Jones, M. Gail; Childers, Gina; Andre, Thomas; Corin, Elysa N.; Hite, Rebecca
ABSTRACT: Creating citizens interested in science and able to participate in science discourse and decisions is one of the goals of science education. Science hobbyists embody this goal through their life-long leisure interests and engagement in science. This study compared the motivations, perceived hobby benefits, and factors that influenced their hobby development for citizen-scientists and non-citizen scientists. A deeper understanding of factors that relate to involvement in both citizen science and science hobbies may inform efforts to encourage such participation. Data were collected through open-ended interviews with 107 amateur astronomer and birder hobbyists (67 citizen scientists and 40 non-citizen science participants) and an online survey. The results of the interviews informed the development of the online survey that was distributed nationally; participants included 2119 non-citizen scientists and 745 citizen scientists. Citizen scientists reported different hobby-related motivations, interests, and experiences than non-citizen science hobbyists. Male citizen scientists were more likely than male non-citizen scientists to report sharing information with others and educating youth as important motives to their hobby participation. As compared to non citizen-scientists, citizen scientists reported being more influenced in their hobby by formal and informal educational institutions, were more likely than non-citizen scientist hobbyists to report publishing articles for the public and using electronic media to communicate with other hobbyists. Citizen scientists reported improved science process skills and a better understanding of the nature of science. The implications of the results for a deeper understanding of what encourages individuals to participate in citizen science and science hobbies are discussed.